PEMBERDAYAAN EKONOMI DESA MELALUI PENGEMBANGAN BUMDES AYAM PETELUR DI DESA NUSA, KECAMATAN AMANUBAN BARAT - barung, leonardus; Adin, Amonius; Carvalo, Antonius Mario; Menggo, Marianus Mario T.J.; Matly, Ave Maria H.S.; Ola, Angelica W.S.; Meivian, Dea; Maulaka, Julia Puiko; Berry, Julita Saptary Weni; Kau, Elisabeth Lasitania; Leki, Aurelia Fiona; Kehi, Bernadina Relia; Poso, Maria Mariana; Kelen, Wilhelmina Theresia; Deo, Santalia Maria; Loda, Adelheid Elisabet (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service program was conducted in Nusa Village, Amanuban Barat Subdistrict, South Central Timor Regency, with the aim of strengthening the role of Village-Owned Enterprises (BUMDes) through the development of a layer chicken farm. The program focused on providing technical assistance, mentoring, and monitoring of egg production management as a sustainable source of village income. Based on field observations and interviews, the egg production during the initial ten days reached 417 eggs, with an estimated average weekly production of 973 eggs and a potential monthly production of 3,892 eggs. These results indicate that BUMDes egg production has significant potential to improve food security and generate additional income for the local community. The findings highlight that proper management, training, and community involvement are critical factors for ensuring the sustainability of BUMDes-based agribusiness in rural areas.